An Exploration of the Implementation and Effectiveness of IT Governance Processes in Institutions of Higher Education in Australia - Bhattacharjya, Jyotirmoyee; Chang, Vanessa (Printsprint, 2006)
Over the past decade, IT governance has become a key issue of concern for senior IT decision makers around the world. This exploratory study examined how IT governance is being implemented through a number of processes, structures and relational mechanisms in four leading institutions of higher education in Australia. This paper will focus particularly on the implementation of IT governance processes in these institutions and examine how internationally recognized standards such as COBIT, ITIL and ISO17799 are being utilized in this implementation. The study reveals a number of findings in the context of the implementation of IT governance processes in the higher education environment.